Flex early evaluation : assessing Flex and your project needs (O'Reilly short cut., 2007)
Evaluating any new technology can be achallenge. This Short Cut is designed tohelp web application developers (andtheir team managers) understand if Flexis the right technology for their companyor client. Although the authors of thisbook have a strong understanding of theFlex framework, this isn't a sales pitchfor Flex. The authors believe that Flex isa good tool to solve many business problems, but it is not a cure-all. After reading this material, you'll knowwhat's good about Rich Internet Applications. You'll know the capabilities ofFlex 2, how Flex works, and how muchit costs. We'll tell y.